Redescription of the African assassin bug Ectomocoris proximus (Hemiptera: Heteroptera: Reduviidae) with a new synonymy - Liu, Yingqi; Webb, Michael D.; Cai, Wanzhi (Zootaxa, 2020)
The African peiratine assassin bug species, Ectomocoris proximus Miller, 1952 (Hemiptera: Heteroptera: Reduviidae) is redescribed and E. limbatus Miller, 1952, syn. nov., is placed as its junior synonym. Types of both nominal species were examined, habitus images and figures of the male genitalia are provided.